Anti-aging effects and mechanisms of kimchi during fermentation under stress-induced premature senescence cellular system - Kim, B.K., Pusan National University, Busan, Republic of Korea; Park, K.Y., Pusan National University, Busan, Republic of Korea; Kim, H.Y., Gyeongnam National University of Science and Technology, Jinju, Republic of Korea; Ahn, S.C., Pusan National University, Busan, Republic of Korea; Cho, E.J., Pusan National University, Busan, Republic of Korea (Food science and biotechnology, 2011)
Aging is known to associate with inflammation that accelerates aging process. The anti-aging activity and the related inflammatory mechanisms of kimchi during fermentation were evaluated using stress-induced premature senescence (SIPS) of WI-38 human fibroblasts caused by hydrogen peroxide (H₂O₂), a well established cellular aging model. The methanol extracts of fresh kimchi (pH 5.8), optimally ripened kimchi (OptR kimchi, pH 4.1), and over ripened kimchi (pH 3.8) fermented at 5℃ were prepared. H₂O₂-treated WI-38 cells showed the loss of cell viability, the increase of lipid peroxidation and shortening of the cell lifespan, indicating the induction of SIPS. However, the treatment of kimchi, especially OptR kimchi, attenuated cellular oxidative stress through increase in cell viability and inhibition of lipid peroxidation. In addition, the lifespan of young-, middle-, and old-aged WI-38 cell was extended, suggesting promising role of kimchi as an anti-aging agent. Furthermore, H₂O₂-treated WI-38 cells significantly increased the age-related inflammatory gene expression such as nuclear factor-κB (NF-κB), cyclooxygenase-2, inducible nitric oxide synthase. However, the treatment of kimchi exerted anti-aging effect through NF-κB-related gene regulation. These results suggest that kimchi, especially OptR kimchi, may delay the aging process by regulation of inflammatory process.